Influence of Availability of Equipment, Learning Aids and Facilities on Practical Abilities of Learners in Physics in Sirisia Division, Bungoma West Sub-County, Kenya - publisher, publisher (African Journal of Education,Science and Technology (AJEST), 2020)
Physics plays an important role in the development of the scientific base necessary for Kenya’s industrialization as envisaged in Vision 2030, but the students’ performance in the subject has been on a downward trend in recent years. This study set out to investigate influence of availability of equipment, learning aids and facilities on the practical skill abilities of the learners in physics during classroom interaction in selected schools in Sirisia Division, Bungoma West Sub-County, Kenya. The research design adopted for the study was descriptive survey. Questionnaires and observation schedules were used to collect the data. The target population for the study was 14 secondary schools, 30 teachers of physics, and form 3 students. One hundred and forty form three students and twelve teachers were selected to fill in the questionnaire. Two physics teachers were observed while teaching a form three class in each of the six schools selected. Data was analyzed using descriptive and inferential statistics, results were presented in tables and percentages and checked off using chi-square. The findings showed that available physics teaching resources influenced learners’ development of practical physics. The study also found out that there was no significant difference between availability of equipments, teaching aids and other facilities and learners’ ability to develop practical physics skills. The study concluded that students who are exposed to inquiry-based learning, in which the teachers’ role is that of a facilitator with the learner playing an active participatory role, develop proficiency in manipulative skills. By making equipment and apparatus available to the learner, the student acquires speed and skill for further education in science and technological field. The study recommends that secondary schools should be empowered to receive more allocation from CDF funds, well-wishers and parents to be able to build standard laboratory (especially the state owned public schools) in which improvised and other concrete materials such as models and specimens could be stored for the purpose of physics teaching through demonstrations, class experiments and project learning. Inspections should be routinely carried out on schools’ laboratories and worn out equipment replaced with new ones.